(untitled) (Revista Tempo e Argumento, 2023)
This paper analyzes the conceptions of Ibero-American secondary school teachers about the role of history teaching in creating collective identities, and how heritage can impact history classes. We applied a peer validated questionnaire to 283 history teachers from seven countries, analyzing their answers using a deductive-inductive method supported by IBM SSPS software (version 23). The analysis reveal that heritage continues to have little presence in lessons, mostly used as an example of historical narratives that highlight the national identity over others.